Lanthanum and manganese co-doped bismuth ferrite film and preparation method thereof
Through the bismuth ferrate film co-doped by lanthanum and manganese and the optimized sol gel process, the problems of leakage current and low residual polarization strength in the bismuth ferrate film are solved, and efficient introduction of doped ions is achieved, which significantly improves the ferroelectric and electrical properties of the film, providing a solid foundation for future device applications.
Patent Information
- Application Number
- CN202411908062.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
AI Technical Summary
The existing bismuth ferrate films have problems with leakage current and low residual polarization strength when applied to devices, and the widely used sol-gel process has limitations in introducing doped ions, and the doping amount is relatively low, resulting in limited inhibition of oxygen vacancy in the film.
A bismuth ferrate film co-doped with lanthanum and manganese is used, and its chemical formula is Bi(1+Z-Y)LaYFe(1-X)MnXO3. By adjusting the molar equivalent of Mn and La, the doping amount of doped ions is increased, and the parameter settings of the sol-gel process are optimized, including adjusting the reaction temperature, time and solvent type to improve the introduction efficiency and uniformity of doped ions.
A bismuth ferrate film with high orientation superiority has excellent ferroelectric properties, significantly reduces leakage current, improves electrical properties, and lays a solid foundation for the widespread application of BFO films in future devices.
Smart Images

Figure CN119683693A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic functional thin film materials, and in particular relates to a lanthanum and manganese co-doped bismuth ferrite film and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of industries such as microelectromechanical systems (MEMS), sensors and random access memory, thin film materials with excellent ferroelectric and piezoelectric properties have become one of the hot topics in the current research field.
[0003] Bismuth ferrite (BiFeO3) is a typical single-phase multiferroic material with a triangular distorted ferromagnetite structure. At room temperature, it is ferroelectrically ordered (TC = 1103K) and antiferromagnetically ordered (TN = 643K), and is one of the few ferromagnetic materials that have both ferroelectricity and antiferromagnetism at room temperature.
[0004] However, in order for BFO thin films to be used in future devices, two major problems must be solved: leakage current and low residual polarization intensity. In recent years, research on bismuth ferrite thin films has mainly focused on how to reduce its leakage current, enhance its ferroelectric properties, and explore its application in more fields. According to relevant reports, the introduction of high-valent ions and lanthanide rare earth elements is a key means to effectively solve the oxygen vacancy problem in BFO thin films, which is crucial to improving the overall performance of the film. However, the widely used sol-gel process has limitations in the introduction of dopant ions, which is specifically manifested in the relatively low doping amount of dopant ions. Therefore, the inhibitory effect on oxygen vacancies in the film is limited, which leads to its insignificant effect in reducing film leakage current and improving electrical properties.
[0005] At the same time, application cost is also a factor that needs to be considered. Seeking a low-cost method to improve the electrical performance of BFO and reduce leakage current is the focus of future development. Summary of the invention
[0006] The present invention aims at solving the above-mentioned technical problems existing in the prior art and proposes a bismuth ferrite film and a low-cost preparation method thereof which can solve the leakage current problem and improve the electrical properties of the film.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A lanthanum and manganese co-doped bismuth ferrite film, the chemical formula of which is Bi (1+Z-Y) La Y Fe (1-X) Mn XO3, wherein X is the molar equivalent of Mn element, 0.09≤X≤0.13, Y is the molar equivalent of La element, 0.12≤Y≤0.18, element Bi is added in excess, Z is the molar equivalent of Bi element, the film has N layers, Z in the first layer is 8%-11%, Z in the second to N-4 layers is 5%-8%, and Z in the N-3 to N layers is 3%-5%; the bismuth source is bismuth nitrate, the lanthanum source is lanthanum nitrate, the iron source is ferric nitrate, and the manganese source is manganese acetate tetrahydrate.
[0009] Preferably, the number of layers of the thin film is 10≤N≤16, and the thickness of each layer of the thin film is 100nm-120nm.
[0010] Preferably, the range of X:Y is 0.64 to 0.8, the range of X is 0.11 to 0.12, and the range of Y is 0.15 to 0.17.
[0011] The preparation method of the above-mentioned lanthanum and manganese co-doped bismuth ferrite film adopts a sol-gel method, which specifically includes the following steps:
[0012] S1. Preparation of precursor solution:
[0013] Weigh ferric nitrate according to the stoichiometric ratio and dissolve it in acetic acid. After it is completely dissolved, add ethylene glycol to the solution to obtain a mixed solution A.
[0014] Weigh lanthanum nitrate according to the stoichiometric ratio and dissolve it in ethanol. After it is completely dissolved, add ethylene glycol methyl ether to the solution to obtain a mixed solution B;
[0015] Introducing mixed solution B into mixed solution A to obtain mixed solution C;
[0016] Add bismuth nitrate and manganese acetate tetrahydrate to the mixed solution C in sequence to obtain a mixed solution D. After stirring the mixed solution D for 0.5 h, ethanol is added to the mixed solution D again to prepare a precursor solution. The prepared precursor solution is placed in an environment with a temperature of 15-18° C. and allowed to stand for 18-24 h for standby use.
[0017] S2. Preparation of thin film materials:
[0018] Using a layer-by-layer annealing process, the first layer of precursor solution is deposited on an ITO / glass substrate by spin coating, and then the substrate is placed on a hot plate for drying, and the dried film is placed in a rapid annealing furnace for a two-stage annealing treatment; then other layers of material are deposited on their respective lower layers in the same manner, and the above spin coating and annealing steps are repeated several times until the film thickness meets the requirements;
[0019] S3, Annealing:
[0020] The thin film material obtained in step S2 is annealed at a temperature in the range of 465° C. to 525° C. for 5 minutes to obtain a lanthanum and manganese co-doped bismuth ferrite thin film.
[0021] Preferably, in step S1, the concentration of the precursor solution is 0.58 mol / L to 0.72 mol / L, and the volume ratio of acetic acid, ethylene glycol, ethanol required for mixed solution B, ethylene glycol methyl ether, and ethanol required for mixed solution D is 4:1.5:2:3:2.5.
[0022] Preferably, in step S2, the drying temperature is 120-130°C, and the drying time is 40s-60s.
[0023] Preferably, in step S2, the two-stage annealing process is: the first stage is 185-205°C, 70-80s, and the heating rate is 20-25°C / min; the second stage is 425-475°C, 100-120s, 8-12°C / min.
[0024] Preferably, in step S2, the spin coating speed of the spin coating method is 3500-4200 rpm, and the time is 18-22 s.
[0025] Compared with the prior art, the advantages and positive effects of the present invention are:
[0026] (1) The present invention provides a lanthanum and manganese co-doped bismuth ferrite film, which has a high orientation preference at a single layer thickness of 100nm-120nm and has excellent ferroelectric properties.
[0027] (2) The present invention realizes co-doping of lanthanum and manganese, and increases the doping amount of doping ions, thereby improving the inhibitory effect on oxygen vacancies in the film, thereby improving its effect in reducing film leakage current and improving electrical properties.
[0028] (3) The present invention optimizes the parameter settings of the sol-gel process, including adjusting the reaction temperature, time, and solvent type, to improve the efficiency and uniformity of the introduction of dopant ions; these methods help achieve higher dopant ion concentrations. Through these measures, we can more effectively suppress oxygen vacancies in BFO films, thereby reducing leakage current and improving electrical properties, laying a solid foundation for the widespread application of BFO films in future devices.
[0029] (4) The present invention realizes the doping of Mn, which is low in cost and simple in operation, and is more conducive to its future industrial application.
[0030] (5) The present invention has achieved a major breakthrough in the annealing process. Its advantages lie in the substantial reduction of the annealing temperature and the significant shortening of the annealing time. By optimizing the annealing process, the present invention not only improves production efficiency, but also takes a solid step in energy conservation and emission reduction, injecting new vitality into the green development of industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The XRD spectrum of the bismuth ferrite film prepared in Example 4 of the present invention;
[0032] Figure 2 This is the hysteresis loop spectrum of the bismuth ferrite film prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] A lanthanum and manganese co-doped bismuth ferrite film, the chemical formula of which is Bi (1+Z-Y) La Y Fe (1-X) Mn X O3, wherein X is the molar equivalent of Mn element 0.09, Y is the molar equivalent of La element 0.18, element Bi is added in excess, Z is the molar equivalent of Bi element, the film has 12 layers, Z is 8% in the first layer, 8% in the second to eighth layers, and 3% in the ninth to twelfth layers; the bismuth source is bismuth nitrate, the lanthanum source is lanthanum nitrate, the iron source is ferric nitrate, and the manganese source is manganese acetate tetrahydrate.
[0036] The thickness of each layer of the thin film is 100 nm.
[0037] The preparation method of the above-mentioned lanthanum and manganese co-doped bismuth ferrite film adopts a sol-gel method, which specifically includes the following steps:
[0038] S1. Preparation of precursor solution:
[0039] Weigh ferric nitrate according to the stoichiometric ratio and dissolve it in acetic acid. After it is completely dissolved, add ethylene glycol to the solution to obtain a mixed solution A.
[0040] Weigh lanthanum nitrate according to the stoichiometric ratio and dissolve it in ethanol. After it is completely dissolved, add ethylene glycol methyl ether to the solution to obtain a mixed solution B;
[0041] Introducing mixed solution B into mixed solution A to obtain mixed solution C;
[0042] Add bismuth nitrate and manganese acetate tetrahydrate to the mixed solution C in sequence to obtain a mixed solution D. After stirring the mixed solution D for 0.5 h, ethanol is added to the mixed solution D again to prepare a precursor solution. The prepared precursor solution is placed in an environment with a temperature of 15-18° C. and allowed to stand for 18 h for standby use.
[0043] S2. Preparation of thin film materials:
[0044] Using a layer-by-layer annealing process, the first layer of precursor solution is deposited on an ITO / glass substrate by spin coating, and then the substrate is placed on a hot plate for drying, and the dried film is placed in a rapid annealing furnace for a two-stage annealing treatment; then other layers of material are deposited on their respective lower layers in the same manner, and the above spin coating and annealing steps are repeated several times until the film thickness meets the requirements;
[0045] S3, Annealing:
[0046] The thin film material obtained in step S2 is annealed at 465° C. for 5 minutes to obtain a lanthanum and manganese co-doped bismuth ferrite thin film.
[0047] In step S1, the concentration of the precursor solution is 0.58 mol / L, and the volume ratio of acetic acid, ethylene glycol, ethanol required for mixed solution B, ethylene glycol methyl ether, and ethanol required for mixed solution D is 4:1.5:2:3:2.5, wherein the total volume of the solution is 130 ml.
[0048] In step S2, the drying temperature is 120°C and the drying time is 40s.
[0049] In step S2, the two-stage annealing process is as follows: the first stage is 185°C, 80s, and the heating rate is 20°C / min; the second stage is 425°C, 120s, and the heating rate is 12°C / min.
[0050] In step S2, the spin coating speed of the spin coating method is 3500 rpm and the time is 22 s.
[0051] Example 2
[0052] A lanthanum and manganese co-doped bismuth ferrite film, the chemical formula of which is Bi (1+Z-Y) La Y Fe (1-X) Mn XO3, wherein X is the molar equivalent of Mn element 0.13, Y is the molar equivalent of La element 0.12, element Bi is added in excess, Z is the molar equivalent of Bi element, the film has 10 layers, Z in the first layer is 11%, Z in the second to sixth layers is 5%, and Z in the seventh to tenth layers is 5%; the bismuth source is bismuth nitrate, the lanthanum source is lanthanum nitrate, the iron source is ferric nitrate, and the manganese source is manganese acetate tetrahydrate.
[0053] The thickness of each layer of the thin film is 100 nm.
[0054] The preparation method of the above-mentioned lanthanum and manganese co-doped bismuth ferrite film adopts a sol-gel method, which specifically includes the following steps:
[0055] S1. Preparation of precursor solution:
[0056] Weigh ferric nitrate according to the stoichiometric ratio and dissolve it in acetic acid. After it is completely dissolved, add ethylene glycol to the solution to obtain a mixed solution A.
[0057] Weigh lanthanum nitrate according to the stoichiometric ratio and dissolve it in ethanol. After it is completely dissolved, add ethylene glycol methyl ether to the solution to obtain a mixed solution B;
[0058] Introducing mixed solution B into mixed solution A to obtain mixed solution C;
[0059] Add bismuth nitrate, manganese acetate tetrahydrate and acetylacetone to the mixed solution C in sequence to obtain a mixed solution D. After stirring the mixed solution D for 0.5 h, ethanol is added to the mixed solution D again to prepare a precursor solution. The prepared precursor solution is placed in an environment with a temperature of 15-18° C. and allowed to stand for 24 h for standby use.
[0060] S2. Preparation of thin film materials:
[0061] Using a layer-by-layer annealing process, the first layer of precursor solution is deposited on an ITO / glass substrate by spin coating, and then the substrate is placed on a hot plate for drying, and the dried film is placed in a rapid annealing furnace for a two-stage annealing treatment; then other layers of material are deposited on their respective lower layers in the same manner, and the above spin coating and annealing steps are repeated several times until the film thickness meets the requirements;
[0062] S3, Annealing:
[0063] The thin film material obtained in step S2 is annealed at 475° C. for 5 minutes to obtain a lanthanum and manganese co-doped bismuth ferrite thin film.
[0064] Preferably, in step S1, the concentration of the precursor solution is 0.62 mol / L, and the volume ratio of acetic acid, ethylene glycol, ethanol required for mixed solution B, ethylene glycol methyl ether, and ethanol required for mixed solution D is 4:1.5:2:3:2.5, wherein the total volume of the solution is 130 ml.
[0065] In step S2, the drying temperature is 130°C and the drying time is 60s.
[0066] The two-stage annealing process is as follows: the first stage is 195°C, 70s, and the heating rate is 25°C / min; the second stage is 445°C, 100s, and the heating rate is 10°C / min.
[0067] In step S2, the spin coating speed of the spin coating method is 3700 rpm and the time is 18 s.
[0068] Example 3
[0069] A lanthanum and manganese co-doped bismuth ferrite film, the chemical formula of which is Bi (1+Z-Y) La Y Fe (1-X) Mn X O3, wherein X is the molar equivalent of Mn element 0.13, Y is the molar equivalent of La element 0.18, element Bi is added in excess, Z is the molar equivalent of Bi element, the film has 16 layers in total, Z is 9% in the first layer, Z is 5% in the second to 12th layers, and Z is 3% in the 13th to 16th layers; the bismuth source is bismuth nitrate, the lanthanum source is lanthanum nitrate, the iron source is ferric nitrate, and the manganese source is manganese acetate tetrahydrate.
[0070] The thickness of each layer of the thin film is 110 nm.
[0071] The preparation method of the above-mentioned lanthanum and manganese co-doped bismuth ferrite film adopts a sol-gel method, which specifically includes the following steps:
[0072] S1. Preparation of precursor solution:
[0073] Weigh ferric nitrate according to the stoichiometric ratio and dissolve it in acetic acid. After it is completely dissolved, add ethylene glycol to the solution to obtain a mixed solution A.
[0074] Weigh lanthanum nitrate according to the stoichiometric ratio and dissolve it in ethanol. After it is completely dissolved, add ethylene glycol methyl ether to the solution to obtain a mixed solution B;
[0075] Introducing mixed solution B into mixed solution A to obtain mixed solution C;
[0076] Add bismuth nitrate and manganese acetate tetrahydrate to the mixed solution C in sequence to obtain a mixed solution D. After stirring the mixed solution D for 0.5 h, ethanol is added to the mixed solution D again to prepare a precursor solution. The prepared precursor solution is placed in an environment with a temperature of 15-18° C. and allowed to stand for 19 h for standby use.
[0077] S2. Preparation of thin film materials:
[0078] Using a layer-by-layer annealing process, the first layer of precursor solution is deposited on an ITO / glass substrate by spin coating, and then the substrate is placed on a hot plate for drying, and the dried film is placed in a rapid annealing furnace for a two-stage annealing treatment; then other layers of material are deposited on their respective lower layers in the same manner, and the above spin coating and annealing steps are repeated several times until the film thickness meets the requirements;
[0079] S3, Annealing:
[0080] The thin film material obtained in step S2 is annealed at 485° C. for 5 min to obtain a lanthanum and manganese co-doped bismuth ferrite thin film.
[0081] Preferably, in step S1, the concentration of the precursor solution is 0.65 mol / L, and the volume ratio of acetic acid, ethylene glycol, ethanol required for mixed solution B, ethylene glycol methyl ether, and ethanol required for mixed solution D is 4:1.5:2:3:2.5, wherein the total volume of the solution is 130 ml.
[0082] In step S2, the drying temperature is 120°C and the drying time is 50s.
[0083] In step S2, the two-stage annealing process is as follows: the first stage is 205°C, 70s, and the heating rate is 22°C / min; the second stage is 455°C, 100s, and the heating rate is 12°C / min;
[0084] In step S2, the spin coating speed of the spin coating method is 3900 rpm and the time is 22 s.
[0085] Example 4
[0086] A lanthanum and manganese co-doped bismuth ferrite film, the chemical formula of which is Bi (1+Z-Y) La Y Fe (1-X) Mn X O3, wherein X is the molar equivalent of Mn element 0.11, Y is the molar equivalent of La element 0.15, element Bi is added in excess, Z is the molar equivalent of Bi element, the film has 12 layers, Z in the first layer is 9%, Z in the second to ninth layers is 6%, and Z in the tenth to twelfth layers is 3%; the bismuth source is bismuth nitrate, the lanthanum source is lanthanum nitrate, the iron source is ferric nitrate, and the manganese source is manganese acetate tetrahydrate.
[0087] The thickness of each layer of the thin film is 110 nm.
[0088] The preparation method of the above-mentioned lanthanum and manganese co-doped bismuth ferrite film adopts a sol-gel method, which specifically includes the following steps:
[0089] S1. Preparation of precursor solution:
[0090] Weigh ferric nitrate according to the stoichiometric ratio and dissolve it in acetic acid. After it is completely dissolved, add ethylene glycol to the solution to obtain a mixed solution A.
[0091] Weigh lanthanum nitrate according to the stoichiometric ratio and dissolve it in ethanol. After it is completely dissolved, add ethylene glycol methyl ether to the solution to obtain a mixed solution B;
[0092] Introducing mixed solution B into mixed solution A to obtain mixed solution C;
[0093] Add bismuth nitrate and manganese acetate tetrahydrate to the mixed solution C in sequence to obtain a mixed solution D. After stirring the mixed solution D for 0.5 h, ethanol is added to the mixed solution D again to prepare a precursor solution. The prepared precursor solution is placed in an environment with a temperature of 15-18° C. and allowed to stand for 22 h for standby use.
[0094] S2. Preparation of thin film materials:
[0095] Using a layer-by-layer annealing process, the first layer of precursor solution is deposited on an ITO / glass substrate by spin coating, and then the substrate is placed on a hot plate for drying, and the dried film is placed in a rapid annealing furnace for a two-stage annealing treatment; then other layers of material are deposited on their respective lower layers in the same manner, and the above spin coating and annealing steps are repeated several times until the film thickness meets the requirements;
[0096] S3, Annealing:
[0097] The thin film material obtained in step S2 is annealed at 505° C. for 5 minutes to obtain a lanthanum and manganese co-doped bismuth ferrite thin film.
[0098] Preferably, in step S1, the concentration of the precursor solution is 0.68 mol / L, and the volume ratio of acetic acid, ethylene glycol, ethanol required for mixed solution B, ethylene glycol methyl ether, acetylacetone, and ethanol required for mixed solution D is 4:1.5:2:3:2.5, wherein the total volume of the solution is 130 ml.
[0099] In step S2, the drying temperature is 130°C and the drying time is 45s.
[0100] In step S2, the two-stage annealing process is as follows: the first stage is 205°C, 70s, and the heating rate is 25°C / min; the second stage is 455°C, 110s, and the heating rate is 9°C / min;
[0101] In step S2, the spin coating speed of the spin coating method is 4000 rpm and the time is 20 s.
[0102] Figure 1 From the XRD spectrum of the prepared bismuth ferrite film, it can be seen that the film has achieved preferential orientation and the film quality is high. Figure 2 The hysteresis loop spectrum of the prepared bismuth ferrite film shows that it has excellent ferroelectric properties.
[0103] Example 5
[0104] A lanthanum and manganese co-doped bismuth ferrite film, the chemical formula of which is Bi (1+Z-Y) La Y Fe (1-X) Mn X O3, wherein X is 0.12 of the molar equivalent of Mn element, Y is 0.16 of the molar equivalent of La element, element Bi is added in excess, Z is the molar equivalent of Bi element, the film has 10 layers in total, Z is 11% in the first layer, 8% in the second to sixth layers, and 5% in the seventh to tenth layers; the bismuth source is bismuth nitrate, the lanthanum source is lanthanum nitrate, the iron source is ferric nitrate, and the manganese source is manganese acetate tetrahydrate.
[0105] The thickness of each layer of the thin film is 120 nm.
[0106] The preparation method of the above-mentioned lanthanum and manganese co-doped bismuth ferrite film adopts a sol-gel method, which specifically includes the following steps:
[0107] S1. Preparation of precursor solution:
[0108] Weigh ferric nitrate according to the stoichiometric ratio and dissolve it in acetic acid. After it is completely dissolved, add ethylene glycol to the solution to obtain a mixed solution A.
[0109] Weigh lanthanum nitrate according to the stoichiometric ratio and dissolve it in ethanol. After it is completely dissolved, add ethylene glycol methyl ether to the solution to obtain a mixed solution B;
[0110] Introducing mixed solution B into mixed solution A to obtain mixed solution C;
[0111] Add bismuth nitrate and manganese acetate tetrahydrate to the mixed solution C in sequence to obtain a mixed solution D. After stirring the mixed solution D for 0.5 h, ethanol is added to the mixed solution D again to prepare a precursor solution. The prepared precursor solution is placed in an environment with a temperature of 15-18° C. and allowed to stand for 24 h for standby use.
[0112] S2. Preparation of thin film materials:
[0113] Using a layer-by-layer annealing process, the first layer of precursor solution is deposited on an ITO / glass substrate by spin coating, and then the substrate is placed on a hot plate for drying, and the dried film is placed in a rapid annealing furnace for a two-stage annealing treatment; then other layers of material are deposited on their respective lower layers in the same manner, and the above spin coating and annealing steps are repeated several times until the film thickness meets the requirements;
[0114] S3, Annealing:
[0115] The thin film material obtained in step S2 is annealed at 525° C. for 5 minutes to obtain a lanthanum and manganese co-doped bismuth ferrite thin film.
[0116] Preferably, in step S1, the concentration of the precursor solution is 0.7 mol / L, and the volume ratio of acetic acid, ethylene glycol, ethanol required for mixed solution B, ethylene glycol methyl ether, acetylacetone, and ethanol required for mixed solution D is 4:1.5:2:3:2.5, wherein the total volume of the solution is 130 ml.
[0117] Preferably, in step S2, the drying temperature is 130° C. and the drying time is 55 s.
[0118] In step S2, the two-stage annealing process is as follows: the first stage is 200°C, 70s, and the heating rate is 24°C / min; the second stage is 455°C, 100s, and the heating rate is 9°C / min;
[0119] In step S2, the spin coating speed of the spin coating method is 3900 rpm and the time is 18 s.
[0120] Example 6
[0121] A lanthanum and manganese co-doped bismuth ferrite film, the chemical formula of which is Bi (1+Z-Y) La Y Fe (1-X) Mn X O3, wherein X is the molar equivalent of Mn element 0.11, Y is the molar equivalent of La element 0.18, element Bi is added in excess, Z is the molar equivalent of Bi element, the film has 12 layers, Z in the first layer is 10%, Z in the second to the ninth layer is 6%, and Z in the tenth to the twelfth layer is 3%; the bismuth source is bismuth nitrate, the lanthanum source is lanthanum nitrate, the iron source is ferric nitrate, and the manganese source is manganese acetate tetrahydrate.
[0122] The thickness of each layer of the thin film is 110 nm.
[0123] The preparation method of the above-mentioned lanthanum and manganese co-doped bismuth ferrite film adopts a sol-gel method, which specifically includes the following steps:
[0124] S1. Preparation of precursor solution:
[0125] Weigh ferric nitrate according to the stoichiometric ratio and dissolve it in acetic acid. After it is completely dissolved, add ethylene glycol to the solution to obtain a mixed solution A.
[0126] Weigh lanthanum nitrate according to the stoichiometric ratio and dissolve it in ethanol. After it is completely dissolved, add ethylene glycol methyl ether to the solution to obtain a mixed solution B;
[0127] Introducing mixed solution B into mixed solution A to obtain mixed solution C;
[0128] Add bismuth nitrate and manganese acetate tetrahydrate to the mixed solution C in sequence to obtain a mixed solution D. After stirring the mixed solution D for 0.5 h, ethanol is added to the mixed solution D again to prepare a precursor solution. The prepared precursor solution is placed in an environment with a temperature of 15-18° C. and allowed to stand for 23 h for standby use.
[0129] S2. Preparation of thin film materials:
[0130] Using a layer-by-layer annealing process, the first layer of precursor solution is deposited on an ITO / glass substrate by spin coating, and then the substrate is placed on a hot plate for drying, and the dried film is placed in a rapid annealing furnace for a two-stage annealing treatment; then other layers of material are deposited on their respective lower layers in the same manner, and the above spin coating and annealing steps are repeated several times until the film thickness meets the requirements;
[0131] S3, Annealing:
[0132] The thin film material obtained in step S2 is annealed at 465° C. for 5 minutes to obtain a lanthanum and manganese co-doped bismuth ferrite thin film.
[0133] Preferably, in step S1, the concentration of the precursor solution is 0.68 mol / L, and the volume ratio of acetic acid, ethylene glycol, ethanol required for mixed solution B, ethylene glycol methyl ether, acetylacetone, and ethanol required for mixed solution D is 4:1.5:2:3:2.5, wherein the total volume of the solution is 130 ml.
[0134] In step S2, the drying temperature is 120°C and the drying time is 50s.
[0135] In step S2, the two-stage annealing process is as follows: the first stage is 185°C, 70s, and the heating rate is 24°C / min; the second stage is 425°C, 100s, and the heating rate is 9°C / min;
[0136] In step S2, the spin coating speed of the spin coating method is 3700 rpm and the time is 18 s.
[0137] Example 7
[0138] A lanthanum and manganese co-doped bismuth ferrite film, the chemical formula of which is Bi (1+Z-Y) La Y Fe (1-X) Mn X O3, wherein X is the molar equivalent of Mn element 0.12, Y is the molar equivalent of La element 0.17, element Bi is added in excess, Z is the molar equivalent of Bi element, the film has 14 layers, Z in the first layer is 10%, Z in the second to the tenth layer is 7%, and Z in the eleventh to the fourth layer is 3%; the bismuth source is bismuth nitrate, the lanthanum source is lanthanum nitrate, the iron source is ferric nitrate, and the manganese source is manganese acetate tetrahydrate.
[0139] The thickness of each layer of the thin film is 120 nm.
[0140] The preparation method of the above-mentioned lanthanum and manganese co-doped bismuth ferrite film adopts a sol-gel method, which specifically includes the following steps:
[0141] S1. Preparation of precursor solution:
[0142] Weigh ferric nitrate according to the stoichiometric ratio and dissolve it in acetic acid. After it is completely dissolved, add ethylene glycol to the solution to obtain a mixed solution A.
[0143] Weigh lanthanum nitrate according to the stoichiometric ratio and dissolve it in ethanol. After it is completely dissolved, add ethylene glycol methyl ether to the solution to obtain a mixed solution B;
[0144] Introducing mixed solution B into mixed solution A to obtain mixed solution C;
[0145] Add bismuth nitrate and manganese acetate tetrahydrate to the mixed solution C in sequence to obtain a mixed solution D. After stirring the mixed solution D for 0.5 h, ethanol is added to the mixed solution D again to prepare a precursor solution. The prepared precursor solution is placed in an environment with a temperature of 15-18° C. and allowed to stand for 19 h for standby use.
[0146] S2. Preparation of thin film materials:
[0147] Using a layer-by-layer annealing process, the first layer of precursor solution is deposited on an ITO / glass substrate by spin coating, and then the substrate is placed on a hot plate for drying, and the dried film is placed in a rapid annealing furnace for a two-stage annealing treatment; then other layers of material are deposited on their respective lower layers in the same manner, and the above spin coating and annealing steps are repeated several times until the film thickness meets the requirements;
[0148] S3, Annealing:
[0149] The thin film material obtained in step S2 is annealed at 465° C. for 5 minutes to obtain a lanthanum and manganese co-doped bismuth ferrite thin film.
[0150] Preferably, in step S1, the concentration of the precursor solution is 0.58 mol / L, and the volume ratio of acetic acid, ethylene glycol, ethanol required for mixed solution B, ethylene glycol methyl ether, and ethanol required for mixed solution D is 4:1.5:2:3:2.5, wherein the total volume of the solution is 130 ml.
[0151] Preferably, in step S2, the drying temperature is 120° C. and the drying time is 40 seconds.
[0152] Preferably, in step S2, the two-stage annealing process is: the first stage is 185°C, 70s, and the heating rate is 23°C / min; the second stage is 425°C, 100s, and the heating rate is 11°C / min;
[0153] Preferably, in step S2, the spin coating speed of the spin coating method is 3500 rpm and the time is 18.
[0154] Example 8
[0155] A lanthanum and manganese co-doped bismuth ferrite film, the chemical formula of which is Bi (1+Z-Y) La Y Fe (1-X) Mn X O3, wherein X is the molar equivalent of Mn element 0.11, Y is the molar equivalent of La element 0.15, element Bi is added in excess, Z is the molar equivalent of Bi element, the film has 13 layers, Z in the first layer is 8%, Z in the second to ninth layers is 7%, and Z in the tenth to thirteenth layers is 4%; the bismuth source is bismuth nitrate, the lanthanum source is lanthanum nitrate, the iron source is ferric nitrate, and the manganese source is manganese acetate tetrahydrate.
[0156] The thickness of each layer of the thin film is 120 nm.
[0157] The preparation method of the above-mentioned lanthanum and manganese co-doped bismuth ferrite film adopts a sol-gel method, which specifically includes the following steps:
[0158] S1. Preparation of precursor solution:
[0159] Weigh ferric nitrate according to the stoichiometric ratio and dissolve it in acetic acid. After it is completely dissolved, add ethylene glycol to the solution to obtain a mixed solution A.
[0160] Weigh lanthanum nitrate according to the stoichiometric ratio and dissolve it in ethanol. After it is completely dissolved, add ethylene glycol methyl ether to the solution to obtain a mixed solution B;
[0161] Introducing mixed solution B into mixed solution A to obtain mixed solution C;
[0162] Add bismuth nitrate and manganese acetate tetrahydrate to the mixed solution C in sequence to obtain a mixed solution D. After stirring the mixed solution D for 0.5 h, ethanol is added to the mixed solution D again to prepare a precursor solution. The prepared precursor solution is placed in an environment with a temperature of 15-18° C. and allowed to stand for 22 h for standby use.
[0163] S2. Preparation of thin film materials:
[0164] Using a layer-by-layer annealing process, the first layer of precursor solution is deposited on an ITO / glass substrate by spin coating, and then the substrate is placed on a hot plate for drying, and the dried film is placed in a rapid annealing furnace for a two-stage annealing treatment; then other layers of material are deposited on their respective lower layers in the same manner, and the above spin coating and annealing steps are repeated several times until the film thickness meets the requirements;
[0165] S3, Annealing:
[0166] The thin film material obtained in step S2 is annealed at 495° C. for 5 minutes to obtain a lanthanum and manganese co-doped bismuth ferrite thin film.
[0167] In step S1, the concentration of the precursor solution is 0.72 mol / L, and the volume ratio of acetic acid, ethylene glycol, ethanol required for mixed solution B, ethylene glycol methyl ether, and ethanol required for mixed solution D is 4:1.5:2:3:2.5, wherein the total volume of the solution is 130 ml.
[0168] In step S2, the drying temperature is 130°C and the drying time is 50s.
[0169] In step S2, the two-stage annealing process is as follows: the first stage is 185°C, 70s, and the heating rate is 21°C / min; the second stage is 425°C, 100s, and the heating rate is 8°C / min;
[0170] In step S2, the spin coating speed of the spin coating method is 3500 and the time is 18s.
[0171] Example 9
[0172] A lanthanum and manganese co-doped bismuth ferrite film, the chemical formula of which is Bi (1+Z-Y) La Y Fe (1-X) Mn X O3, wherein X is the molar equivalent of Mn element 0.09, Y is the molar equivalent of La element 0.18, element Bi is added in excess, Z is the molar equivalent of Bi element, the film has 10 layers, Z in the first layer is 9%, Z in the second to sixth layers is 5%, and Z in the seventh to tenth layers is 5%; the bismuth source is bismuth nitrate, the lanthanum source is lanthanum nitrate, the iron source is ferric nitrate, and the manganese source is manganese acetate tetrahydrate.
[0173] The number of layers of the thin film is 10, and the thickness of each layer of the thin film is 100 nm.
[0174] The preparation method of the above-mentioned lanthanum and manganese co-doped bismuth ferrite film adopts a sol-gel method, which specifically includes the following steps:
[0175] S1. Preparation of precursor solution:
[0176] Weigh ferric nitrate according to the stoichiometric ratio and dissolve it in acetic acid. After it is completely dissolved, add ethylene glycol to the solution to obtain a mixed solution A.
[0177] Weigh lanthanum nitrate according to the stoichiometric ratio and dissolve it in ethanol. After it is completely dissolved, add ethylene glycol methyl ether to the solution to obtain a mixed solution B;
[0178] Introducing mixed solution B into mixed solution A to obtain mixed solution C;
[0179] Add bismuth nitrate and manganese acetate tetrahydrate to the mixed solution C in sequence to obtain a mixed solution D. After stirring the mixed solution D for 0.5 h, ethanol is added to the mixed solution D again to prepare a precursor solution. The prepared precursor solution is placed in an environment with a temperature of 15-18° C. and allowed to stand for 23 h for standby use.
[0180] S2. Preparation of thin film materials:
[0181] Using a layer-by-layer annealing process, the first layer of precursor solution is deposited on an ITO / glass substrate by spin coating, and then the substrate is placed on a hot plate for drying, and the dried film is placed in a rapid annealing furnace for a two-stage annealing treatment; then other layers of material are deposited on their respective lower layers in the same manner, and the above spin coating and annealing steps are repeated several times until the film thickness meets the requirements;
[0182] S3, Annealing:
[0183] The thin film material obtained in step S2 is annealed at 500° C. for 5 minutes to obtain a lanthanum and manganese co-doped bismuth ferrite thin film.
[0184] In step S1, the concentration of the precursor solution is 0.62 mol / L, and the volume ratio of acetic acid, ethylene glycol, ethanol required for mixed solution B, ethylene glycol methyl ether, and ethanol required for mixed solution D is 4:1.5:2:3:2.5, wherein the total volume of the solution is 130 ml.
[0185] In step S2, the drying temperature is 120°C and the drying time is 40s.
[0186] In step S2, the two-stage annealing process is as follows: the first stage is 205°C, 70s, and the heating rate is 23°C / min; the second stage is 455°C, 100s, and the heating rate is 12°C / min;
[0187] In step S2, the spin coating speed of the spin coating method is 3700 rpm and the time is 18 s.
[0188] Example 10
[0189] The difference from Example 4 is that Y is 0.19 of the molar equivalent of La. The other conditions remain unchanged.
[0190] Comparing the hysteresis loop spectrum with that of Example 4, it is found that the difference is not large, which may be because the La doping amount has been saturated.
[0191] Embodiment 11
[0192] The difference from Example 4 is that X is 0.14 molar equivalent of Mn element. The other conditions remain unchanged.
[0193] Example 12
[0194] The difference from Example 4 is that X is 0.08 of the molar equivalent of the Mn element. The other conditions remain unchanged.
[0195] Comparing the samples obtained in Examples 11 and 12 with those in Example 4, it was found that the film quality was not high, cracks appeared in all of them, and it was not easy to succeed.
Claims
1. A lanthanum and manganese co-doped bismuth ferrite film, characterized in that: Its chemical formula is Bi (1+Z-Y) La Y Fe (1-X) Mn X O3, wherein X is the molar equivalent of Mn element, 0.09≤X≤0.13, Y is the molar equivalent of La element, 0.12≤Y≤0.18, element Bi is added in excess, Z is the molar equivalent of Bi element, the film has N layers, Z in the first layer is 8%-11%, Z in the second to N-4 layers is 5%-8%, and Z in the N-3 to N layers is 3%-5%; the bismuth source is bismuth nitrate, the lanthanum source is lanthanum nitrate, the iron source is ferric nitrate, and the manganese source is manganese acetate tetrahydrate.
2. The lanthanum and manganese co-doped bismuth ferrite film according to claim 1, characterized in that: The number of layers of the film is 10≤N≤16, and the thickness of each layer of the film is 100nm-120nm.
3. The lanthanum and manganese co-doped bismuth ferrite film according to claim 1, characterized in that: The range of X:Y is 0.64 to 0.8, the range of X is 0.11 to 0.12, and the range of Y is 0.15 to 0.
17.
4. The method for preparing the lanthanum and manganese co-doped bismuth ferrite film according to any one of claims 1 to 3, characterized in that: The specific steps include: S1. Preparation of precursor solution: Weigh ferric nitrate according to the stoichiometric ratio and dissolve it in acetic acid. After it is completely dissolved, add ethylene glycol to the solution to obtain a mixed solution A. Weigh lanthanum nitrate according to the stoichiometric ratio and dissolve it in ethanol. After it is completely dissolved, add ethylene glycol methyl ether to the solution to obtain a mixed solution B; Introducing mixed solution B into mixed solution A to obtain mixed solution C; Add bismuth nitrate and manganese acetate tetrahydrate to the mixed solution C in sequence to obtain a mixed solution D. After stirring the mixed solution D for 0.5 h, ethanol is added to the mixed solution D again to prepare a precursor solution. The prepared precursor solution is placed in an environment with a temperature of 15-18° C. and allowed to stand for 18-24 h for standby use. S2. Preparation of thin film materials: Using a layer-by-layer annealing process, the first layer of precursor solution is deposited on an ITO / glass substrate by spin coating, and then the substrate is placed on a hot plate for drying, and the dried film is placed in a rapid annealing furnace for a two-stage annealing treatment; then other layers of material are deposited on their respective lower layers in the same manner, and the above spin coating and annealing steps are repeated several times until the film thickness meets the requirements; S3, Annealing: The thin film material obtained in step S2 is annealed at a temperature in the range of 465° C. to 525° C. for 5 minutes to obtain a lanthanum and manganese co-doped bismuth ferrite thin film.
5. The method for preparing a lanthanum and manganese co-doped bismuth ferrite film according to claim 4, characterized in that: In step S1, the concentration of the precursor solution is 0.58 mol / L to 0.72 mol / L, and the volume ratio of acetic acid, ethylene glycol, ethanol required for mixed solution B, ethylene glycol methyl ether, and ethanol required for mixed solution D is 4:1.5:2:3:2.
5.
6. The method for preparing a lanthanum and manganese co-doped bismuth ferrite film according to claim 4, characterized in that: In step S2, the drying temperature is 120-130°C, and the drying time is 40s-60s.
7. The method for preparing a lanthanum and manganese co-doped bismuth ferrite film according to claim 4, characterized in that: In step S2, the two-stage annealing process is as follows: the first stage is 185-205°C, 70-80s, and the heating rate is 20-25°C / min; The second stage: 425-475℃, 100-120s, heating rate is 8-12℃ / min.
8. The method for preparing lanthanum and manganese co-doped bismuth ferrite thin film according to claim 4, characterized in that: In step S2, the spin coating speed of the spin coating method is 3500-4200 rpm, and the time is 18-22 s.